Sustainable Development Reporting and Financial Performance: Systematic Literature Review 2019-2024 - Esmeralda, Angel II P. (MID Publisher International, 2025)
This systematic literature review examines the relationship between sustainable development reporting (SDR) and corporate financial performance (CFP), synthesizing empirical evidence from studies published between 2019 and 2024. The review addresses the ongoing debate regarding whether sustainability disclosure creates or destroys shareholder value. Following PRISMA 2020 guidelines, this review analyzed 88 peer-reviewed empirical articles from Scopus, Web of Science, and Google Scholar. Studies were categorized by relationship direction, performance metrics used, reporting frameworks examined, and contextual moderators. The majority of studies (59%) report a positive relationship between SDR and CFP, supporting stakeholder theory and signaling theory. Mixed results (27%) suggest the relationship is contingent on moderating factors including firm size, industry, geographic region, and reporting quality. Negative relationships (9%) are primarily associated with short-term cost perspectives. GRI-aligned reporting and external assurance strengthen the positive SDR-CFP relationship. Market-based measures (Tobin’s Q) show stronger positive associations than accounting-based measures (ROA, ROE). This review provides a comprehensive framework integrating SDR dimensions, transmission mechanisms, and performance outcomes. It identifies critical moderating factors and offers actionable insights for practitioners while highlighting gaps for future research, including the need for longitudinal studies and investigation of SDG-specific reporting impacts.